Advances of Bibframe in 2014 - Agenjo, Xavier; Hernández-Carrascal, Francisca (Anuario ThinkEPI, 2015)
The progress made by the Bibliographic framework initiative (Bibframe) in 2014 is described. Developments are related to the consolidation of Bibframe at the organizational level, as an element of cooperation between institutions, including those who have different views on linked open data such as OCLC and the Library of Congress. The implementers list has been greatly expanded, making it possible to evaluate Bibframe for various new applications. Finally, advances in the Bibframe data model and in tools available to test this model are summarized.